Early Onset of Selective Serotonin Reuptake Inhibitor Antidepressant Action - Taylor, Matthew J.; Freemantle, Nick; Gedde, John R.; Bhagwagar, Zubin (Archives of General Psychiatry, 2006)
Context: Selective serotonin reuptake inhibitors (SSRIs) are often described as having a delayed onset of effect in the treatment of depression. However, some trials have reported clinical improvement as early as the first week of treatment. Objective: To test the alternative hypotheses of delayed vs early onset of antidepressant action with SSRIs in patients with unipolar depression. Data Sources: Trials identified by searching CENTRAL, The Cochrane Collaboration database of controlled trials (2005), and the reference lists of identified trials and other systematic reviews. Study Selection: Randomized controlled trials of SSRIs vs placebo for the treatment of unipolar depression in adults that reported outcomes for at least 2 time points in the first 4 weeks of treatment (50 trials from >500 citations identified). Trials were excluded if limited to participants older than 65 years or specific comorbidities. Data Extraction: Data were extracted on trial design, participant characteristics, and outcomes by a single reviewer. Data Synthesis: Pooled estimates of treatment effect on depressive symptom rating scales were calculated for weeks 1 through 6 of treatment. In the primary analysis, the pattern of response seen was tested against alternative models of onset of response. The primary analysis incorporated data from 28 randomized controlled trials (n = 5,872). A model of early treatment response best fit the experimental data. Treatment with SSRIs rather than placebo was associated with clinical improvement by the end of the first week of use. A secondary analysis indicated an increased chance of achieving a 50% reduction in Hamilton Depression Rating Scale scores by 1 week (relative risk, 1.64; 95% confidence interval, 1.2-2.25) with SSRI treatment compared with placebo. Conclusions: Treatment with SSRIs is associated with symptomatic improvement in depression by the end of the first week of use, and the improvement continues at a decreasing rate for at least 6 weeks. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: Adult; Age Factors; Antidepressant Drugs; Confidence Intervals; Depressive Disorder; Double-Blind Method; Drug Therapy; Humans; Major Depression; Middle Aged; Placebos; Psychiatric Status Rating Scales; Randomized Controlled Trials as Topic; Research Design; Reuptake; Risk; Serotonin Reuptake Inhibitors; Serotonin Uptake Inhibitors; Time Factors; Treatment Outcome; antidepressant action; depression; early onset; selective serotonin reuptake inhibitor